Otoscopy Findings - Rebol, Janez; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book is intended to serve as a practical guide to effective ear examination. Learning to perform otoscopy is not easy because the external auditory canal is obstructed by cerumen, otorrhea can be present, and the tympanic membrane is sometimes only partially visible. In children, it is even more difficult because of the narrow ear canal, the alignment of the tympanic membrane, and the restlessness of the child. Uncertainty in diagnosis can lead to overtreatment, as in the case of acute otitis media and unnecessary prescription of antibiotics. On the other hand, delay in diagnosis may lead to severe complications such as mastoiditis, meningitis and brain abscess in case of overlooked middle ear cholesteatoma. This textbook aims to facilitate learning through a wealth of full color otoscopic pictures and is divided into chapters that cover the major otologic pathologies. The volume includes images related to cochlear implants and bone conduction devices, along with the images of the major surgical procedures or conditions associated with them. It also helps the reader to identify the conditions in which surgical intervention is mandatory. Given its didactic approach, this guide will be an invaluable resource for medical students and residents in otolaryngology, and in paediatrics and general medicine alike.
1.Otoscopy -- 2.Middle ear,. 3. diseases of the external auditory canal: Cerumen. Cysts of the external auditory canal. Exostoses and osteomas. Foreign bodies in the external auditory canal. Bullous myringitis. Granulomatous myringitis. Herpes zoster oticus (Ramsey Hunt syndrome). Otomycosis. Diffuse otitis externa. 4. Secretory otitis media -- 5.Adhesive otitis -- 6.Acute and chronic otitis: Definition. Risk factors. Pathophysiology. Recurrent acute otitis. Tympanosclerosis -- 7.Cholesteatoma -- 8.Fractures of the temporal bone -- 9.Paragangliomas of the temporal bone -- 10.Cochlear implants -- 11. BCD (bone conduction devices) -- 12.Conditions after operations.
Keywords: Otorhinolaryngology; Pediatrics; Family medicine; Otorhinolaryngology; Pediatrics; General Practice and Family Medicine; Ear Diseases -- diagnosis; Otoscopy -- methods; Otoscopes